2020
DOI: 10.1097/aud.0000000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Listening Difficulties of Children With Cochlear Implants in Mainstream Secondary Education

Abstract: Objectives: Previous research has shown that children with cochlear implants (CIs) encounter more communication difficulties than their normal-hearing (NH) peers in kindergarten and elementary schools. Yet, little is known about the potential listening difficulties that children with CIs may experience during secondary education. The aim of this study was to investigate the listening difficulties of children with a CI in mainstream secondary education and to compare these results to the difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Todorov et al (2021) compared the observed and the self-reported engagement of 16 students who are Deaf or hardof-hearing (DHH) attending mainstream schools to that of matched controls with typical hearing. They express that when compared to their hearing peers in mainstream classrooms, students who are DHH experience more listening difficulties as cited by (Krijger et al, 2020). They echo that this challenge may have implications for their engagement in the classroom.…”
Section: Introductionmentioning
confidence: 96%
“…Todorov et al (2021) compared the observed and the self-reported engagement of 16 students who are Deaf or hardof-hearing (DHH) attending mainstream schools to that of matched controls with typical hearing. They express that when compared to their hearing peers in mainstream classrooms, students who are DHH experience more listening difficulties as cited by (Krijger et al, 2020). They echo that this challenge may have implications for their engagement in the classroom.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, individuals who use a CI understand less when listening to recorded speech than when hearing live speech [ 10 ]. This is all in addition to the loss of visual cues that are crucial for speech understanding, especially when listening without real-time captioning [ 11 ]. Individuals with hearing loss, even those with CI, still need visual cues and non-verbal information to fully understand speech, but these are often absent when communicating virtually [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, many children who are deaf or hard of hearing (D/HH) can develop substantial receptive and expressive spoken language skills (e.g., Geers & Sedey, 2011;Moeller, 2000;Nicholas & Geers, 2006;Yoshinaga-Itano, 2003). Research has shown that early intervention positively effects children's auditory receptive abilities and their possibility to integrate into a mainstream school (Govaerts et al, 2002;Krijger, Coene, Govaerts, & Dhooge, 2020). In the Netherlands, like in most countries, there has been a shift toward the enrolment of children who are D/HH, into mainstream schools, rather than in segregated special schools or special classes (Stinson & Antia, 1999).…”
mentioning
confidence: 99%
“…Furthermore, acoustic and auditory factors have been identified as problematic for children who are D/HH in mainstream primary and secondary education. Poor classroom acoustics negatively affects their performance and well-being (e.g., Crandell & Smaldino, 2000;Klatte, Hellbrück, Seidel, & Leistner, 2010) and the limited access to or disturbance of the auditory signal cause more listening difficulties for students with CI (Krijger et al, 2020).…”
mentioning
confidence: 99%